EU stimulus packages. Estimating the size of the European stimulus packages for 2009: an update - David Saha; Jakob von Weizsäcker (Bruegel, 2009)
David Saha and Jakob von Weizsäcker present the latest breakdown of the fiscal stimuli in the 13 largest EU economies and compare the total European package for 2009 to the US stimulus package. The authors estimate the size of the European stimulus packages to increase to 0.99% of GDP following increases in the stimulus packages in the Netherlands, the UK and Germany . The US stimulus package is estimated at about 1.7 percent of GDP, substantially above the EU average but only marginally above the largest national stimulus package in the EU.
Keywords: 330; Konjunkturpolitik; Öffentliche Ausgaben; EU-Finanzen; EU-Staaten